Chemical composition and major volatile compounds of the hydrolyzed product from Kappaphycus alvarezii by-products using flavourzyme - Anh, Nguyen Phuong; Ky, Pham Xuan; Ha, Dao Viet; Ha, Dao Viet; Hong, Nguyen Thu; Hy, Le Ho Khanh; Thiet, Doan Thi; Vy, Phan Bao (Vietnam Journal of Marine Science and Technology, 2019)
The chemical composition of flavourzyme hydrolysis product from Kappaphycus alvarezii by-products was analyzed. The results showed that the protein hydrolysate powder had high content of proteins (21.66%) and low content of lipids (0.22%). Hydrolyzed products contained about 15 free amino acids with relatively high content of some amino acids such as aspartic acid (1,879 mg/100 g), glutamic acid (1,813 mg/100 g), glycine (1,121 mg/100 g), tyrosine (1,203 mg/100 g) ) and serine (3,165 mg/100 g). In addition, main volatile flavor compounds such as acetophenone; nonanal; indole; 2.4-di-tert-butylphenol; heptadecane; 6.10.14- trimethylpentadecan-2-one have also been discovered. As a result, the by-products of K. alvarezii take a potential role in the food industry.